Evidence of hawksbill turtle (Eretmochelys imbricata) depredation on fish caught in gillnets - Yusuf C. El-Khaled; Carlos M. Duarte; Raquel S. Peixoto (Frontiers in Marine Science, 2023)
Bycatch is a major global threat to marine megafauna and occurs in nearly all fishing fleets, including small-scale fisheries that use gillnets. Gillnets represent a threat to endangered air-breathing megafauna, who incidentally entangle in bottom-set gillnets and suffocate after being attracted by bait that is secured on fishing gear. We here provide the first evidence that hawksbill turtles feed on trapped fish in gillnets, suggesting that potential prey items trapped in gillnets may act as additional bait, attracting carnivorous sea turtles towards this threat. This overlooked depredating behaviour potentially explains and increases the likelihood of critically endangered hawksbill turtle bycatch in gillnet fisheries, calling for technological and management solutions.